2021
DOI: 10.7759/cureus.15070
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of MDMA (3,4-Methylenedioxymethamphetamine) for Post-traumatic Stress Disorder in Humans: A Systematic Review and Meta-Analysis

Abstract: Background : 3,4-methylenedioxymethamphetamine (MDMA), known recreationally as “Molly” or “Ecstasy”, is a triple monoamine reuptake inhibitor. MDMA specifically acts as a weak 5-HT1 and 5-HT2 receptor agonist, targeting 5-HT 2A , 5-HT 2B , and 5-HT 2C receptors. Its potential use for therapeutic purposes with these pharmacological profiles remains a controversial subject. Studies have shown the potential benefits in clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
10
0
5
Order By: Relevance
“…In these studies, participants received MDMA in one or a handful of nondirective, supportive psychotherapy sessions, with multiple nondrug sessions preceding and following each drug session for preparation and integration. Across more than 600 experimental sessions, MDMA was found to be safe and well tolerated, with only one serious adverse event deemed possibly related to drug administration (increase in premature ventricular contractions without significant long-term sequalae) 12 . Mild treatment-associated adverse events were more common in the MDMA arm of the phase 3 study, with the most common being muscle tightness, decreased appetite, and nausea 10 …”
Section: 4-methylenedioxymethamphetamine–assisted Therapy For Ptsdmentioning
confidence: 99%
See 3 more Smart Citations
“…In these studies, participants received MDMA in one or a handful of nondirective, supportive psychotherapy sessions, with multiple nondrug sessions preceding and following each drug session for preparation and integration. Across more than 600 experimental sessions, MDMA was found to be safe and well tolerated, with only one serious adverse event deemed possibly related to drug administration (increase in premature ventricular contractions without significant long-term sequalae) 12 . Mild treatment-associated adverse events were more common in the MDMA arm of the phase 3 study, with the most common being muscle tightness, decreased appetite, and nausea 10 …”
Section: 4-methylenedioxymethamphetamine–assisted Therapy For Ptsdmentioning
confidence: 99%
“…Long-term follow-up data from the same 6 studies found a large within-subjects effect size of d = 1.58 at treatment exit (1–2 months after the last active dose MDMA session) compared with baseline, which further improved between treatment exit and long-term follow-up (approximately 1 year later) with a small effect size of d = 0.23 14 . A recent meta-analysis including 10 phase 2 trials found a large overall effect size of d = 0.93 when comparing active MDMA intervention versus control groups, with a relative risk for remission of 2.96 (95% confidence interval, 1.63–5.39) indicating a nearly 3-fold higher chance of remission in the MDMA group 12 . Finally, in the only phase 3 study to date, Mitchell and colleagues demonstrated significant improvement in PTSD symptoms with MDMA-assisted therapy 10 .…”
Section: 4-methylenedioxymethamphetamine–assisted Therapy For Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-traumatic stress disorder (PTSD) is a complex mental disorder that affects 7.7 million adults in the United States annually, with one in 11 individuals being diagnosed with PTSD at some point in their lives. More than twice as many women (10%) as men (4%) have PTSD, with sexual assault being the most common traumatic incidence [ 1 ]. According to the DSM-5 criteria, PTSD is a mental health disorder that can develop after exposure to a traumatic event, such as death, serious injury, or sexual violence [ 2 ].…”
Section: Introductionmentioning
confidence: 99%